The Language of Influence: Analyzing Lexical Density and Readability in Political Editorials Across Leading Newspapers - Br Sembiring, Franinta Egia D. R; Nadya Elchaira; Dzikri Ilma; Nurlela (IJLHE: International Journal of Language, Humanities, and Education, 2024)
This research examines lexical density and readability in election-related editorials from five major international newspapers: The Guardian, The Washington Post, The Sydney Morning Herald, The Oberlin Review, and The Los Angeles Times. Lexical density, the ratio of content words to total words, indicates linguistic complexity, while readability scores reflect accessibility. The Guardian exhibits the highest lexical density (60.02%), followed by The Washington Post (58.14%), reflecting a preference for precise, complex language. In contrast, The Sydney Morning Herald has the lowest density (54.74%), suggesting greater accessibility. Readability assessments categorize most editorials as “difficult” or “fairly difficult,” with The Guardian, The Sydney Morning Herald, and The Oberlin Review requiring advanced reading skills due to intricate vocabulary and lengthy sentences. These findings reveal distinct editorial objectives. Newspapers like The Guardian cater to an analytical readership seeking in-depth analysis, while outlets such as The Sydney Morning Herald prioritize readability, potentially appealing to a broader audience. The study underscores the importance of linguistic choices in shaping audience engagement, influencing accessibility, and impacting readers’ perceptions of political content. Varying complexity levels suggest that editorial strategies align with the ideological and demographic goals of each publication.